Digital preservation in 2009 - Térmens, Miquel (Anuario ThinkEPI, 2010)
The international state of research and development of digital preservation solutions in 2009 is assessed, as well as the expectations for 2010. We pay particular attention to the monitoring of the main research and development of specific software, and feature prominent research centres worldwide.